Revisiting the Saccharomyces cerevisiae predicted ORFeome - Li, Qian-Ru; Carvunis, Anne-Ruxandra; Yu, Haiyuan; Han, Jing-Dong J.; Zhong, Quan; Simonis, Nicolas; Tam, Stanley; Hao, Tong; Klitgord, Niels J.; Dupuy, Denis; Mou, Danny; Wapinski, Ilan; et al.

(untitled) (Genome Research, 2008)
Accurately defining the coding potential of an organism, i.e., all protein-encoding open reading frames (ORFs) or “ORFeome,” is a prerequisite to fully understand its biology. ORFeome annotation involves iterative computational predictions from genome sequences combined with experimental verifications. Here we reexamine a set of Saccharomyces cerevisiae “orphan” ORFs recently removed from the original ORFeome annotation due to lack of conservation across evolutionarily related yeast species. We show that many orphan ORFs produce detectable transcripts and/or translated products in various functional genomics and proteomics experiments. By combining a naïve Bayes model that predicts the likelihood of an ORF to encode a functional product with experimental verification of strand-specific transcripts, we argue that orphan ORFs should still remain candidates for functional ORFs. In support of this model, interstrain intraspecies genome sequence variation is lower across orphan ORFs than in intergenic regions, indicating that orphan ORFs endure functional constraints and resist deleterious mutations. We conclude that ORFs should be evaluated based on multiple levels of evidence and not be removed from ORFeome annotation solely based on low sequence conservation in other species. Rather, such ORFs might be important for micro-evolutionary divergence between species.